2018
DOI: 10.1038/s41598-018-26817-3
|View full text |Cite
|
Sign up to set email alerts
|

First Radiological Study of a Complete Dental Ontogeny Sequence of an Extinct Equid: Implications for Equidae Life History and Taphonomy

Abstract: The sequence of cheek teeth mineralization, eruption, and replacement of an extinct horse species is here documented with radiological techniques for the first time thanks to the exceptional preservation of Hipparion sp. mandibles from Cerro de los Batallones (Madrid Basin, Spain). The sequence of dental ontogeny in mammals provides valuable insights about life history traits, such as the pace of growth, and about the mode of formation of fossiliferous assemblages. We have determined that the order of permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…However, this is not always the case since there are other factors on which life history traits depend and that are associated with an organism's ecology (Sibly and Brown, 2007;Stearns, 1992). Indeed, the pace of growth of hipparionins has recently been questioned based on the study of their molar eruption sequence interpreted within the context of Schultz's Rule (Domingo et al, 2018). Grounded on the idea that the…”
Section: A C C E P T E D Mmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is not always the case since there are other factors on which life history traits depend and that are associated with an organism's ecology (Sibly and Brown, 2007;Stearns, 1992). Indeed, the pace of growth of hipparionins has recently been questioned based on the study of their molar eruption sequence interpreted within the context of Schultz's Rule (Domingo et al, 2018). Grounded on the idea that the…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…permanent premolars) is typically found in slow-growing taxa (Smith, 2000). Domingo et al (2018), therefore, suggested that hipparionins might have followed a slow pace of growth due to their late third molar eruption, which occurs prior to the appearance of the fourth premolar in some extant equids (Easley et al, 2005;Hoppe et al, 2004;Joubert, 1972;Lkhagvasuren et al, 2013;Smuts, 1974). Recent studies, however, claim that the eruption sequence is more influenced by phylogeny than by life history in primates (Monson and Hlusko, 2018a) and artiodactyls (Monson and Hlusko, 2018b;Veitschegger and Sánchez-Villagra, 2016), challenging the predictive value of the Schultz's Rule.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…To avoid inaccuracies in teeth eruption times resulting from differences between breeds and types of horses, neither ponies nor breeds that differed from the general dental aging system have been employed in the study. Radiography has been widely used in horses for diagnoses and treatment purposes [2,4,21,22], and it can also provide valuable information from fossil sites about the life history, the age at death of the individuals and the evolution of past species [20]. In the present study, intraoral radiographs of the maxillary incisor arcades were used for selection purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Equine teeth, pertaining to the high crowned hypsodont teeth, are subjected to continuous dental wear [ 18 ], and the process of change from deciduous to permanent dentition involves a complex mechanism of development of the dental germs. Time of radiographic appearance and grade of development of dental germs are well-known for deciduous and permanent cheek teeth [ 19 , 20 ], but very few data are available for incisor teeth [ 21 , 22 ]. The latest studies focus on the disorders involving the incisive bone, maxillary incisors, and periodontal structures and show very few radiographic data of dental germs of the permanent incisors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent of vegetation cover at BAT is unclear, due to the absence of significant botanical remains. Herbivore and carnivore d 13 C and d 18 O values for medium and large-sized mammals suggest a similar woodland to mesic C3 grasslands, without significant changes in either the vegetation cover or the hydrological regime during the time separating LVF and BAT-1 and 3 (Domingo et al, 2016(Domingo et al, , 2017. Among musteloids -ailurids, mustelids and mephitids -the samples of ailurids and mephitids are completely different between CLL and BAT at the generic level (Table 3).…”
Section: Remarks On the Batallones Musteloid Guildmentioning
confidence: 97%